An evaluation rate of accidents risks because of rocks falling in rock quarries - Rodríguez Z., Juan M. (2006)
In Galicia can be found around 280 quarries and open pits excavated in rock, most of them are ornamental rock and construction aggregates exploitations. 6100 people work in these mines and 35% are exposed to rock fall accidents; this percentage increases up 80% for the case of aggregates quarries. This phenomenon is now in the work safety statistics. The present work is part of wider project sponsored by the Xunta de Galicia (España) through the University of Vigo, ETSI de Minas, entitled «An index to assess the risk of accident due to rock fall in Galician quarries», where an empirical method to evaluate that risk (ROFRAQ) has been created and is being now fine tuned, with the aim of detecting the riskier slopes and propose corrective measures in order to improve the safety standards. Within this frame, the work here presented analyzes two of these quarries, adding more than 35 new slopes to the information existing so far.